Metabolic Syndrome among NAFLD Patients: A Single-Center Prospective Observational Study in A South Indian Teritary Care Hospital - Khanna, Dayabaran Kiran; Billah, Abdul Ajeed Mohathasim; Govindaraji, Kesava Moorthy; Sebastine, Kaiser Tony; Ashok, Nikita; Baskar, Rakshaya; Anuraman, Jeyavarshini; Suresh, Keerthana; Sundar, Monika Mohana (Indian Journal of Pharmacy Practice)
Background: Non-Alcoholic Fatty Liver Disease (NAFLD) is characterized by abnormal hepatic cholesterol accumulation, leading to metabolic disturbances and chronic liver conditions. The liver’s role in glucose, cholesterol, and toxin regulation highlights the need for early intervention. With a projected 30% prevalence, NAFLD is a growing public health concern, particularly among diabetics and female in India (9-32%). It is strongly linked to metabolic syndrome, obesity, hyperlipidemia, and insulin resistance, increasing mortality risks. Materials and Methods: This study investigates the prevalence of metabolic syndrome in NAFLD patients and assesses the severity of steatosis using ultrasonography criteria. This prospective observational study was conducted over six months (September 2018-March 2019) at the master health checkup in hospital. Ultrasonography confirmed hepatic steatosis, and metabolic parameters (lipid profile, glucose levels) were recorded. Results: Among 136 NAFLD patients, 77.9% (n=106) were diagnosed with metabolic syndrome based on NCEP/ATP-III Criteria. The majority of patients were male (n=87), and metabolic syndrome prevalence was higher among males (81.6%) compared to females (71.4%). Common metabolic abnormalities included increased waist circumference (84.5%), low HDL levels (76.4%), and elevated fasting blood sugar (71.3%). Ultrasonography grading showed Grade I steatosis in 74.2%, Grade II in 25% and Grade III in 0.73% of patients. A significant correlation (p<0.05) was observed between NAFLD and metabolic syndrome components, highlighting a strong association with obesity, dyslipidemia, and insulin resistance. Conclusion: NAFLD is strongly linked to metabolic syndrome, especially in males. Early lifestyle intervention and multidisciplinary care are essential to prevent further complications.
Keywords: Liver Function Tests; Metabolic Syndrome; NAFLD; Obesity; Ultrasonography